Catalytic Oxidation and Depolymerization of Lignin in Aqueous Ionic Liquid - Das, Lalitendu; Xu, Siquan; Shi, Jian (Frontiers in Energy Research, 2017)
Lignin is an integral part of the plant cell wall which provides rigidity to plants, also contributes to the recalcitrance of the lignocellulosic biomass to biochemical and biological deconstruction. Lignin is a promising renewable feedstock for aromatic chemicals; however, an efficient and economic lignin depolymerization method needs to be developed to enable the conversion. In this study, we investigated the depolymerization of alkaline lignin in aqueous 1-ethyl-3-methylimidazolium acetate [C2C1Im][OAc] under oxidizing conditions. Seven different transition metal catalysts were screened in presence of H2O2 as oxidizing agent in a batch reactor. CoCl2 and Nb2O5 proved to be the most effective catalysts in degrading lignin to aromatic compounds. A central composite design was used to optimize the catalyst loading, H2O2 concentration and temperature for product formation. Results show that lignin was depolymerized and the major degradation products found in the extracted oil were guaiacol, syringol, vanillin, acetovanillone, and homovanillic acid. Lignin streams were characterized by Fourier transform infrared spectroscopy (FTIR) and gel permeation chromatography (GPC) to determine the effects of the experimental parameters on lignin depolymerization. The weight average molecular weight (Mw) of liquid stream lignin after oxidation, for CoCl2 and Nb2O5 catalysts were 1202 and 1520 g·mol-1, lower than that of Kraft lignin. Polydispersity index of the liquid stream lignin increased as compared with Kraft lignin, indicating wide span of the molecular weight distribution as a result of lignin depolymerization. Results from this study provide insights into the role of aqueous ionic liquid in presence of the oxidant and transition metal catalysts and the oxidative degradation reaction sequence of lignin towards product formation.